Evaluation of MicroRNA375 as a Novel Biomarker for Graft Damage in Clinical Islet Transplantation. Issue 8 (August 2015) - Kanak, Mazhar A.; Takita, Morihito; Shahbazov, Rauf; Lawrence, Michael C.; Chung, Wen Yuan; Dennison, Ashley R.; Levy, Marlon F.; Naziruddin, Bashoo
Abstract : Background: Early and sensitive detection of islet graft damage is essential for improving posttransplant outcomes. MicroRNA 375 (miR375) has been reported as a biomarker of pancreatic β-cell death in small animal models. Methods: The miR375 levels were measured in purified human islets, sera from patients with autologous and allogeneic islet transplantation as well as total pancreatectomy alone (nontransplanted group). The miR375 levels were also determined in a miniaturized in vitro tube model comprising human islets and autologous blood. Results: The miR375 expression level in islets was dose-dependent ( P < 0.001) and significantly elevated after islet damage in plasma in the in vitro model ( P = 0.003). Clinical analysis revealed that circulating miR375 levels in both autologous and allogeneic islet recipients were significantly elevated for 7 days after islet infusion, compared with the nontransplanted group ( P = 0.005 and <0.001, respectively). Furthermore, miR375 detected the difference in islet graft damage among 3 different anti-inflammatory protocols for clinical autologous transplantation ( P < 0.01). Conclusions: Circulating miR375 can be a reliable biomarker to detect graft damage in clinical islet transplantation because serum C-peptide and proinsulin levels are difficult to interpret due to the influence of multiple factors, such as β-cell stress and physiological response. Abstract : The study of in vitro and clinical scenarios suggests that circulating miR375 shoud be explored further as a biomarker to detect graft damage in clinical islet transplantation. Supplemental digital content is available in the text.